Optimization Strategy to Solve Transmission Interruption Caused by Satellite-Ground Link Switching - Jirui Zhang; Shibing Zhu; Hefeng Bai; Changqing Li (IEEE Access, 2020)
Low earth orbit (LEO) satellite systems, an important part of the next generation of global communication systems, have the advantages of low transmission delay, low satellite cost and low launch cost. The construction of an LEO satellite network with global coverage has become the direction of future space network transmission development. Although extensive research has been conducted on the routing of LEO satellite networks, most papers focus on only space segment routing, with little attention paid to the route between the satellite and ground station. This paper introduces the transmission scenario of ground station switching with connected satellites and analyzes the problem of data packet loss caused by ground station and satellite communication link switching. Two optimization strategies based on static routing and dynamic routing are proposed as solutions to the problem of data packet loss, with software-simulated test results showing that both approaches can effectively avoid packet loss.